2001
DOI: 10.1016/s1470-2045(01)00558-7
|View full text |Cite
|
Sign up to set email alerts
|

Esthesioneuroblastoma: a meta-analysis and review

Abstract: Our objective was to review recent developments in diagnosis, staging, and treatment of esthesioneuroblastoma (ENB). A meta-analysis of publications between 1990 and 2000 was carried out, and studies were classified according to their main subject: origin/aetiology of ENB, histopathological diagnosis, and treatment. Data so far point to the basal progenitor cells of the olfactory epithelium as the origin of ENB. Histopathological diagnosis remains difficult and is based on results of antigen expression detecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

33
714
5
88

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 541 publications
(840 citation statements)
references
References 75 publications
(174 reference statements)
33
714
5
88
Order By: Relevance
“…Debido a que la resección de la lesión no impide su recurrencia, en general se recomienda el uso de radioterapia adyuvante para disminuir el riesgo de recidiva local y locorregional 1,12 . En una serie descrita por Ward y cols 13 , el uso de radioterapia posoperatoria aumentaría la sobrevida libre de enfermedad del 27% al 83% a 5 años.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Debido a que la resección de la lesión no impide su recurrencia, en general se recomienda el uso de radioterapia adyuvante para disminuir el riesgo de recidiva local y locorregional 1,12 . En una serie descrita por Ward y cols 13 , el uso de radioterapia posoperatoria aumentaría la sobrevida libre de enfermedad del 27% al 83% a 5 años.…”
Section: Discussionunclassified
“…como "esthesioneuroepithelionie olfactil" y su origen es controvertido. Dada la histología de la lesión, la teoría más aceptada propone su origen desde el neuroepitelio olfatorio 1 . El estesioneuroblastoma es un tumor muy infrecuente, representando 3% a 5% de las neoplasias sinonasales 2 .…”
Section: Introductionunclassified
“…Currently, this is the most widely utilized staging system in an effort to stratify ONB and continues to serve as a reliable prognosticator of outcome and long-term patient survivability [9]. Hyams et al developed a four-tiered grading system, which has also shown good overall correlation with outcome, demonstrating a histologic continuum from Grade 1 to Grade IV [9,10]. Definitive separation between histologic grades can, at times, be somewhat arbitrary and subject to inter-observer variability.…”
Section: Discussionmentioning
confidence: 99%
“…Definitive separation between histologic grades can, at times, be somewhat arbitrary and subject to inter-observer variability. Therefore, it may be more reliable to separate tumors into low or high grade for prognostic purposes [5,9,10]. Grade I tumors are the most differentiated and often demonstrate sheets of ''small, round, blue cells'' with a high nuclear to cytoplasmic ratio.…”
Section: Discussionmentioning
confidence: 99%
“…ENB should be treated aggressively with surgery and radiation therapy and those with advanced stages even with combination including chemotherapy. Dulgerov et al 10 did a meta analysis of reports on ENB from 1990 to 2000 and they found that survival in Hyams' grades I-II was 56% compared with 25% in grades III-IV. In patients with metastases in cervical lymph nodes (on average 5% of the total) survival was 29%, compared with 64% for patients with N0 disease.…”
Section: Biology Of Tumoursmentioning
confidence: 99%